Perlindungan Hukum Pelaku Usaha Atas Ajuan Pengembalian Dana Dengan Bukti Tidak Memadai Di Shopee - Windy Nauli Sabbastine; Hariyo Sulistiyantoro (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2026)
The technology of information has accelerated the growth of electronic transactions through e-commerce platforms such as Shopee, but it has also given rise to legal challenges in resolving disputes between businesses and consumers. One of the main issues is the filing of refund requests without returning the goods, accompanied by insufficient evidence, which causes losses for businesses. This study employs a normative legal method with a legislative and conceptual approach, supported by literature reviews and interviews, to analyze the legal protection provided to businesses in addressing such unfounded refund requests. Shopee's platform policies regarding the refund process without returning the goods, which are often abused by consumers, still create an imbalance between consumers and businesses due to weak evidence verification mechanisms and limited response times for businesses. The research findings indicate the importance of aligning Shopee's platform policies with applicable laws and regulations, as well as strengthening dispute resolution mechanisms to make legal efforts and legal protection for businesses more effective and fair, and to promote the application of the principle of good faith in electronic transactions.